Three Essays on Empirical Asset Pricing in International Equity Markets - Müller, Birgit Charlotte (Gabler Theses,, 2021)
In this Open-Access-book three essays on empirical asset pricing in international equity markets are presented. Despite being of fundamental economic and scientific importance, international financial markets have remained considerably underresearched until today. In the first essay, the role of firm-specific characteristics is analyzed for the momentum effect to exist in international equity markets. The second essay investigates the validity, persistence, and robustness of the newly discovered capital share growth factor across international equity markets as proposed by Lettau et al. (2019) for the U.S. market. Lastly, the third and final essay studies stock market reactions of European vendor banks to distressed loan sale announcements. About the author Birgit Charlotte Müller pursued her PhD from the Technical University of Darmstadt at the Chair of Corporate Finance. While pursuing her PhD, she additionally worked as a research associate at the Technical University of Munich and the German Graduate School of Management and Law. Additionally, she worked as a lecturer in Mathematics at the Heilbronn University of Applied Sciences.